2022
DOI: 10.3390/polym14061237
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Content in D Isomer and Incorporation of SBA-15 Silica on the Crystallization Ability and Mechanical Properties in PLLA Based Materials

Abstract: Two L-rich polylactides (PLLA) with distinct contents in D isomer and their composites with an intermediate amount of mesoporous Santa Barbara Amorphous-15 (SBA-15) (about 9 wt.%) particles were attained by melt extrusion for the evaluation of the effect of content in D isomer and incorporation of mesoporous silica on the structural PLLA features and on their ultimate mechanical performance. For that, samples have been crystallized under dynamic and isothermal tests (from the melt and from the glassy states). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 64 publications
1
16
0
Order By: Relevance
“…[ 29,30 ] Content in the PLA of D stereoisomer is the key parameter. [ 40 ] As mentioned above, the disordered α ′ modification is attained for this PLA grade at temperatures below ≈90 °C, [ 40 ] while the pure α form is achieved for temperatures above ≈110 °C, observing mixed proportions of the two polymorphs in the temperature interval in between those two values. From the results in Figure 3b, it can be anticipated that the PLA and the mmPLASBA8 should give, under the present cooling rates, a mixture of the two polymorphs, except for the cooling rate of 1 °C min −1 , where the ordered α modification could be expected.…”
Section: Resultsmentioning
confidence: 74%
See 4 more Smart Citations
“…[ 29,30 ] Content in the PLA of D stereoisomer is the key parameter. [ 40 ] As mentioned above, the disordered α ′ modification is attained for this PLA grade at temperatures below ≈90 °C, [ 40 ] while the pure α form is achieved for temperatures above ≈110 °C, observing mixed proportions of the two polymorphs in the temperature interval in between those two values. From the results in Figure 3b, it can be anticipated that the PLA and the mmPLASBA8 should give, under the present cooling rates, a mixture of the two polymorphs, except for the cooling rate of 1 °C min −1 , where the ordered α modification could be expected.…”
Section: Resultsmentioning
confidence: 74%
“…It can be observed that the profiles for the solution‐mixed composites are close to the values reported for the ordered α modification of PLA. [ 40,53 ] Thus, the spacings for the main 110/200 diffraction are presented in Table 1 , being those found in the solution‐mixed samples very near to the one of 0.5286 nm described for the α lattice.…”
Section: Resultsmentioning
confidence: 77%
See 3 more Smart Citations